2006
DOI: 10.1093/jjco/hyl019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Risk Factors for Seroma Formation in Breast Surgery

Abstract: Although a number of factors have been correlated with seroma formation, strong evidence is still scarce. However, there is evidence showing that sentinel lymph node biopsy reduces seroma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 55 publications
10
116
0
9
Order By: Relevance
“…These findings correlate with the study done by Ackroyd et al and Bonnema et al that revealed no correlation between seroma formation and the total amount of drained serous fluid [24,33]. In contrast, Katsumasa et al had reported a positive association between seroma formation and drainage volume during the initial three postoperative days [34]. Also, Tadych et al found a significant relationship between the total hospital drain output and the frequency of seroma after modified radical mastectomy [3].…”
Section: Archives Of Clinical and Experimental Surgerysupporting
confidence: 85%
“…These findings correlate with the study done by Ackroyd et al and Bonnema et al that revealed no correlation between seroma formation and the total amount of drained serous fluid [24,33]. In contrast, Katsumasa et al had reported a positive association between seroma formation and drainage volume during the initial three postoperative days [34]. Also, Tadych et al found a significant relationship between the total hospital drain output and the frequency of seroma after modified radical mastectomy [3].…”
Section: Archives Of Clinical and Experimental Surgerysupporting
confidence: 85%
“…The reported incidence of seroma formation varies widely between 15 and 18% [2]. There are several factors implicated in seroma formation like the extent of lymph node clearance, number of positive nodes, the use of postoperative radiation and whether intraoperative lymphatic channel ligation was done or not, but opinion differs as to their individual role in its pathogenesis [2,3]. The main pathophysiology of seroma is still poorly understood and remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence showing that sentinel lymph node biopsy reduces seroma formation. 17 The study conducted by van Heurn and brink in 1995 on 40 patients concluded that low vacuum drains were removed earlier than high vacuum drains. However, seroma production was not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%